Melatonin and arbuscular mycorrhizal fungi synergistically improve drought toleration in kiwifruit seedlings by increasing mycorrhizal colonization and nutrient uptake - Xia, Hui; Yang, Chunguo; Liang, Yan; He, Zunzhen; Guo, Yuqi; Lang, Yuxuan; Wei, Jie; Tian, Xinbo; Lin, Lijin; Deng, Honghong; Wang, Jin; Lv, Xiulan; et al. (Frontiers in Plant Science, 2022)
Kiwifruit is a vine fruit tree that is vulnerable to water deficiency due to its shallow root system and large leaves. Although mycorrhizal inoculation and melatonin application has been proved to improve plants drought tolerance, their interaction effects are still unclear. In this study, arbuscular mycorrhizal (AM) fungi incubation and melatonin (MT) irrigation were applied to kiwifruit seedlings alone or in combination to investigate their effect on drought tolerance. The results revealed that AM had more effect on promoting root biomass, water use efficiency, and uptake of nitrogen, phosphorus and iron. While MT was more effective in promoting shoot biomass and antioxidant enzyme activities to remove reactive oxygen species accumulation. Moreover, MT supplementary significantly increased the AM colonization, spore density and hyphal length density in roots. Therefore, combined application of AM fungi and MT had additive effects on improvement biomass accumulation, increasing chlorophyll content, photosynthetic efficiency, catalase activity, and decreasing malondialdehyde accumulation under drought stress, thus promoting plant growth and alleviating the drought damage to plant. These results provide guidance for AM and MT combined application to improve abiotic resistance in plants.